The effect of QBO on foE - Atıcı, R.; Sağır, S. (Elsevier Ltd, 2017)
In the present work, the relationship with QBO of difference (?foE = foE mea  ? foE IRI ) between critical frequency (foE) values of ionospheric E-region, measured at Darwin and Casos Island stations and calculated by IRI-2012 ionospheric model, is statistically investigated. A multiple regression model is used as statistical tool. The “Dummy” variables (“DummyWest” and “DummyEast” represent westerly QBO values and easterly QBO values, respectively) are added to model in order to see the effect of westerly and easterly QBO. In the result of calculations, it is observed that the changes in ?foE about 50–52% can be explained by QBO at both stations. The relationship between QBO and ?foE is negative at both stations. The change of 1 ms ?1 in whole set of QBO leads to a decrease of 0.008 MHz at Casos Island station and 0.017 MHz at Darwin station in ?foE. Directions of QBO have an effect on ?foE at the Darwin station, but they've not any effect on ?foE at Casos Island station. It is thought that the difference values in the foE are due to not to be included in the IRI-model of all parameters affecting the critical frequency value. Thus, QBO which is not included to IRI-model can have an effect on foE and more accurate results can be obtained by IRI model if the QBO is included in this model calculations. © 2016 COSPAR
Keywords: A multiple regression model; Critical frequency; Ionospheric E-region; IRI; QBO